Clinical epidemiological profile of spinal cord injury in a rehabilitation center in Teresina, Piauí (Research, Society and Development, 2025)
The objective of this study was to evaluate the causes and etiologies of injuries, identify the clinical and demographic profile of patients, and compare the clinical evolution of different types of injuries. For this purpose, a cross-sectional, descriptive study with a quantitative design was carried out through the analysis of medical records of patients treated at a Rehabilitation Center in Teresina-PI in the period between November 2023 and February 2024. Aspects such as clinical profile and sociodemographic variables, such as gender, race, marital status, and age group, were collected from the medical records. A total of 51 cases were analyzed in the capital of Piauí. The prevalence was of male individuals aged 18 to 30 years old. It was also observed that traumatic injury was the most prevalent in the sample, with 45 cases. It was possible to note that there was a variation in the level of the injury, with 18 cases at the cervical level, 13 at the lumbar level, and 20 at the thoracic level. Regarding urinary incontinence, it was noted that most patients presented this condition upon admission. Furthermore, the main mechanism of spinal cord injury in the patients analyzed was through traffic accidents, followed by spinal cord injury caused by gunshot wounds. It was concluded that in the sample analyzed, there was a higher prevalence of injury at the thoracic level, accompanied by urinary incontinence upon admission, and the main cause was traumatic (traffic accidents).